Evaluation of possible mechanisms of Cordia dichotoma fruits for hyperlipidemia controlling in Wistar albino rats - El-Newary, Samah A.; Wink, Michael (Asian Pacific journal of tropical biomedicine, 2018)
Objective: To investigate the antioxidant capacity of aqueous extract from Cordia dichotoma (C. dichotoma) fruits in-vitro and their effect on nutritional parameters in rats fed on high-fat diet. Methods: In-vitro antioxidant capacity of C. dichotoma extract were evaluated and compared to two standard materials, ascorbic acid and butylated hydroxytoluene. Metabolic experiments were set out using rats fed on high-fat diet. The extract was tested with two dosages: 0.5 and 1.0 g/kg body weight/ day for four weeks. Lipid constituents of diet and faeces and lipid profile of serum and liver were determined. Results: The administration of the C. dichotoma extract with two dosages caused a significant improvement in the lipid metabolism of rats, compared to the hyperlipidemic control which showed significant disturbance in lipid profile. C. dichotoma extract reduced total body weight gain and total feed intake, and enhanced the fresh and dry weight of faecal excretion. The superior effect was recorded with the high dosage of extract. C. dichotoma minimized fat and cholesterol intake significantly and maximized those in faecal excretions in comparison with hyperlipidemic control values, and low dosage was better than the high one. C. dichotoma extract at two dosages normalized the lipid profile of the serum and liver compared with hyperlipidemic control. Conclusions: The protective effect of C. dichotoma extract against hyperlipidemia may be attributed to the reduced ability of an animal to ingest and absorb fat and cholesterol, and enhanced ability to get rid of them in faecal excretion.
Gesehen am 21.10.2018